Bit selection method based on the rock drillability characteristics and principal component analysis of rock-breaking indicators - Yang Hu; Xian Xinlong; Zhou Penggao; Li Zhen; Wei Ruihua; Liang Junqiao; Xiong Shilong (Heliyon)
Ultra-deep oil and gas structure is the key field of exploration and development in the southern margin of Junggar Basin. In this area, the formation lithology is complex, the rock strength is high, and the drilling engineering has problems such as low penetration rate and long drilling cycle. Therefore, the indoor test of core mechanical parameters was carried out, and the logging inversion model of seven rock mechanics and anti-drilling characteristic parameters in the deep strata of the southern margin of Junggar Basin was established by nonlinear multiple regression method. The distribution law of rock mechanics and anti-drilling characteristics of 11 typical wells in the southern margin was analyzed, and the strata were stratified according to rock mechanics and anti-drilling characteristics. At the same time, the comprehensive method is used to select the drill bit, and the actual drilling data of 11 typical wells in the southern margin are statistically analyzed. Based on the principal component method, the actual drilling data of the drill bit in each layer are analyzed, and the high-efficiency drill bit model is optimized. Corresponding to the rock mechanics and anti-drilling characteristic parameters of the drilled formation, a database of high-efficiency drill bit models for drilling in the southern margin of the Junggar Basin was established. This method was applied to two wells in the Hutubi anticline. The recommended high impact and anti-wear drill bits (GT55S, SI516 and MDI516) have an average footage of 35.2 %, 37.8 % and 39.3 % higher than that of adjacent wells in the deep Cretaceous and Jurassic, respectively. Wells Hu 101 and Hu 102 have an average rate of penetration of 1.46 m/h and 1.70 m/h in the deep formations, respectively, which is 15.9 % and 34.9 % higher than the average rate of penetration of 1.26 m/h in the deep formations of the adjacent wells. The practice shows that the high-efficiency drill bit database based on rock mechanical properties and rock breaking indexes provides an effective technical reference for rapid drilling of deep wells in the southern margin of Junggar Basin.